Criteria for selecting open web-oriented technologies for teaching the basics of programming to future software engineers - Tetiana Vakaliuk; Oleg Spirin; Valerii Kontsedailo (Academy of Cognitive and Natural Sciences, 2021)
The article presents the criteria for selecting open web-oriented technologies for teaching the basics of programming to future software engineers. An analysis of the available open web-oriented technologies for teaching the basics of programming to future software engineers made it possible to divide them into compilers, automated systems for checking programming tasks, mind maps, and massive open online courses. Criteria and corresponding indicators are defined for each of them: for web-oriented compilers and mind maps, design and functional criteria are allocated, for web-oriented automated systems for checking programming tasks, design, information-didactic, and communication criteria are allocated, for massive open online courses - informational didactic and functional. Comparative tables are given for all the listed web-oriented technologies for teaching the basics of programming to future software engineers according to certain criteria and indicators.